Effect of biofertilizers on growth of jackfruit (Artocarpus heterophyllus L.) and soil nutrients in South-East Rajasthan (IASH Indian Journal of Arid Horticulture, 2025)
The soil application of different microbial consortia significantly influenced the growth, development, and soil nutrient status of jackfruit (Artocarpus heterophyllus L.) cv. Singapore Jack in South-East Rajasthan. Among the various treatments, the application of T6 (a combination of Azospirillum, PSB, and KSB, 75g each per plant) was found to be significantly superior. The T6 treatment resulted in notable improvements in growth and development parameters, including an 8.05% increase in rootstock girth, 15.0% in scion girth, 69.0% in plant height, 70.0% in the number of nodes per plant, 178.10% in the number of leaves per plant, a 22.92% increase in leaf area, and a chlorophyll content of 41.25 mg/100g in leaves. Additionally, T6 demonstrated superiority in enhancing soil health parameters viz., organic carbon content (0.61%), available nitrogen (326.33 kg/ha), phosphorus (36 kg/ha), and potassium (309.0 kg/ha).